A novel N-doped carbon nanomaterial – carbon nano-mousse. Issue 9 (9th February 2023) - Lesňák, Michal; Cvejn, Daniel; Petr, Martin; Peikertová, Pavlína; Gabor, Roman; Fördös, Tibor; Czernek, Pavel; Plachá, Daniela
Abstract : A novel N-doped carbon material was obtained using a CVD-like procedure by depositing medium-sized pyridine-based molecules on copper-based substrates. Abstract : A novel N-doped carbon material was obtained using a CVD-like procedure by depositing medium-sized pyridine-based molecules on copper-based substrates. The resulting material is a system of interconnected multi-wall carbon nanospheres (approx. 200 nm in diameter) with substantial N-doping (up to 14.8 atom% according to XPS). This material was named "nano-mousse" as it resembles the mousse on champagne in the electron microscopy images. A series of N-doped carbon nano-mousses were prepared by varying the temperature and precursor of the procedure. All of the nano-mousses were characterized by XPS and Raman microspectroscopy. Selected samples were further studied by several types of electron microscopies and spectroscopic ellipsometry. As it appears, N-doped carbon nano-mousses have metal-like properties in terms of optical conductivity and other optical properties, along with macroscopic appearance. XPS and Raman microspectroscopy revealed that their structure and chemical composition is highly dependent on both the nature of the precursor and preparation conditions.